TLR7 agonist in combination with Salmonella as an effective antimelanoma immunotherapy - Vola, Magdalena (2018)
Aim: We evaluated a novel approach combining the use of attenuated Salmonella immunotherapy with a Toll-like receptor agonist, imiquimod, in B16F1 melanoma-bearing mice. Materials & methods: B16F1 melanoma-bearing mice were daily treated with topical imiquimod in combination with one intratumoral injection of attenuated Salmonella enterica serovar Typhimurium LVR01. Results: The combined therapy resulted in retarded tumor growth and prolonged survival. Combination treatment led to an enhancement in the expression of pro-inflammatory cytokines and chemokines in the tumor microenvironment, with a Th1-skewed profile, resulting in a broad antitumor response. The induced immunity was effective in controlling the occurrence of metastasis. Conclusion: Salmonella LVR01 immunotherapy in combination with imiquimod is a novel approach that could be considered as an effective antimelanoma therapy.